2023
DOI: 10.1055/a-2018-2781
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-induced Alterations of the Patellar Tendon in Elite Sprint Track Cyclists

Abstract: The study aims to investigate morphological and mechanical properties and echogenicity of the patellar tendon (PT) after acute fatigue-induced alterations in sprint track cyclists. Fourteen elite track cyclists participated in this study. The exercise protocol consisted of three (on a distance of 62.5 m), one (125 m and 250 m) maximal start accelerations, and sprints from the standing start. Immediately after testing all measurements, PT stiffness and thickness were set at 5-10-15-20 mm distal from the apex of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…The reason for different recovery could be explained by different muscle load (Csapo et al 2011 ). Still, our results showed that repetitive sprints did not enable full recovery 1-h post-exercise of morphological properties and architecture of the quadriceps muscles regardless of the cycling cadence underlining risk of overuse (Klich et al 2023 ). In summary, we observed greater alterations in morphological properties and muscle architecture, especially in VL at optimal cadence compared with 70% of optimal cadence.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The reason for different recovery could be explained by different muscle load (Csapo et al 2011 ). Still, our results showed that repetitive sprints did not enable full recovery 1-h post-exercise of morphological properties and architecture of the quadriceps muscles regardless of the cycling cadence underlining risk of overuse (Klich et al 2023 ). In summary, we observed greater alterations in morphological properties and muscle architecture, especially in VL at optimal cadence compared with 70% of optimal cadence.…”
Section: Discussionmentioning
confidence: 79%
“…There was also a significant increase in QT and PT thickness immediately after the sprint cycling protocol at an optimal cadence contrary to the findings reported in previous review papers (Obst et al 2013 ; Tardioli et al 2012 ). We have previously reported an increase in these tendons after fatigue-induced protocol (Klich et al 2023 ), and after individual pursuit races (Klich et al 2020 ). This observation could be explained by the high-intensity loads leading to tendons thickening (Fisker et al 2017 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation